Examining the Impact of Economic Policy on the Lives of People with Disabilities in Indonesia (Study in Klantingsari Village) - Dicky Putra Surya Pradana; David Maulana; Rayhan Ahmad Alfarizki; Arrafi Rahmad Auliansyah; Andri Maulana (Jurnal Ilmu Manajemen Profitability, 2025)
This study compares the financial health of Bank Muamalat, a national private Islamic bank, and Bank Syariah Indonesia (BSI), a state-owned Islamic bank, based on their 2022 annual financial statements. The analysis applies the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital) to assess their financial performance. Using a quantitative comparative approach, the study evaluates key financial indicators from secondary data sourced from the Financial Services Authority (OJK). The findings reveal that Bank Muamalat demonstrated strong liquidity and capital adequacy but faced challenges in profitability, particularly in return on assets (ROA). In contrast, Bank Syariah Indonesia exhibited superior risk management and operational efficiency, leading to a higher composite score. In 2022, Bank Muamalat received a composite rating of 68.57% (PK-3, "Quite Healthy"), while Bank Syariah Indonesia obtained a higher rating of 74.28% (PK-2, "Healthy"). These differences indicate variations in their financial health and strategic positioning within the Islamic banking sector. The study highlights the need for profitability enhancement at Bank Muamalat and sustained risk management improvements at Bank Syariah Indonesia. Future research should incorporate macroeconomic factors such as inflation and regulatory changes and expand the comparison to other Islamic banks in Southeast Asia to gain a broader industry perspective.